Prevalence and clinical characteristics of earlobe crease in systemic sclerosis: Possible association with vascular dysfunction. Issue 8 (18th May 2020) - Sekiguchi, Akiko; Inoue, Yuta; Yamazaki, Sahori; Uchiyama, Akihiko; Ishikawa, Osamu; Kuribayashi, Shiko; Uraoka, Toshio; Hara, Kenichiro; Yamaguchi, Kouichi; Maeno, Toshitaka; Uchida, Mitsuo; Koyama, Hiroshi; et al.
Abstract: Patients with systemic sclerosis (SSc) develop various vasculopathy‐induced vascular disorders such as Raynaud's phenomenon, abnormal nail‐fold capillaries, persistent digital ischemia, digital ulcers (DU), and sometimes develop renal crisis and pulmonary artery hypertension (PAH), affecting prognosis. Earlobe crease (ELC), also known as Frank's sign, is a wrinkle extending from the tragus to the outer border of the earlobe and is generally recognized as the sign of cardiovascular events. However, no previous study analyzed the association between ELC and SSc. In this study, we examined the prevalence and clinical characteristics of ELC in SSc patients. We analyzed 145 Japanese SSc patients and found that the prevalence of ELC in SSc patients was 23.4% (43/145), similar to that previously reported in the general population without SSc. Using univariate analysis, we found that SSc patients with ELC were characterized by old age, high incidence of DU, ILD and PAH, and high complication of coronary artery diseases (CAD) compared with SSc patients without ELC. In multivariate analysis, ELC was significantly associated with old age and incidence of DU. PAH tended to correlate with ELC without statistical significance. These results suggest that ELC may be associated with vascular disorders in SSc patients. This is the first report concerning the prevalence and clinical characteristics of ELC in patients with SSc. ELC is very easy to detect in clinical practice and helps physicians to identify SSc patients at risk of developing vascular disorders such as DU and PAH.